Animasi Pengenalan Karakter Jurig Leled Samak - Syah, Encep Zainul; Kasmana, Kankan (Fakultas Desain Universitas Komputer Indonesia, 2021)
Folk stories are stories that are passed down from generation to generation, from one generation to the next but are not recorded. Folklore is also a branch of folklore that develops in society. In Indonesia a lot of folklore that developed, especially in Sundanese society and one of the stories told by the Sundanese people is a myth about jurig. It is said that jurig is a person who comes from the spirit of a person who died in an unnatural way. But now there are lots of folktales about suspicions in Sundanese society that have started to fade away just like the story about Jurig Leled Samak. Therefore this design aims to re-introduce the story of Jurig Leled Samak itself by using animation in the form of motion graphics.